2018
DOI: 10.1101/424549
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Deeply conserved susceptibility in a multi-host, multi-parasite system

Abstract: Variation in susceptibility is ubiquitous in multi‐host, multi‐parasite assemblages, and can have profound implications for ecology and evolution in these systems. The extent to which susceptibility to parasites is phylogenetically conserved among hosts can be revealed by analysing diverse regional communities. We screened for haemosporidian parasites in 3983 birds representing 40 families and 523 species, spanning ~ 4500 m elevation in the tropical Andes. To quantify the influence of host phylogeny on infecti… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(25 citation statements)
references
References 94 publications
3
20
2
Order By: Relevance
“…Contrary to previous studies demonstrating an increase of prevalence with increasing elevation across the tropical Andes (Barrow et al, ; Galen & Witt, ; González et al, ; Harrigan et al, ; Lotta et al, ), we have shown no effect of altitude on infection probability and phylogenetic diversity of Leucocytozoon across bird communities at a continental scale. This pattern may be driven by the scarcity of Leucocytozoon infections in the highland Atlantic Forest and the moderate prevalence of Leucocytozoo n in some low‐elevation sites such as the Pantanal and temperate forest.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Contrary to previous studies demonstrating an increase of prevalence with increasing elevation across the tropical Andes (Barrow et al, ; Galen & Witt, ; González et al, ; Harrigan et al, ; Lotta et al, ), we have shown no effect of altitude on infection probability and phylogenetic diversity of Leucocytozoon across bird communities at a continental scale. This pattern may be driven by the scarcity of Leucocytozoon infections in the highland Atlantic Forest and the moderate prevalence of Leucocytozoo n in some low‐elevation sites such as the Pantanal and temperate forest.…”
Section: Discussioncontrasting
confidence: 99%
“…We used these host traits because they are known to influence haemosporidian diversity and prevalence and are available in open‐source data repositories. The predicted effects of these traits specifically on Leucocytozoon infection have been debated previously (Barrow et al, ; Lutz et al, ). As sex information was missing for 1,424 birds, we imputed these missing values using Bernoulli draws with a prior belief of p = .5.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nuthatches also had very low prevalence; we did detect infections in five of 80 birds (6.25%) by PCR, but found no gametocytes in thin blood smears, suggesting that these might represent abortive infections of atypical hosts (Olias et al 2011; Moens et al 2016). At the clade level, suboscines were the least infected, a pattern that has been demonstrated consistently and has been used to illustrate that susceptibility to haemosporidians is evolutionarily conserved (Ricklefs 1992; Barrow et al 2019). Corvides was the most infected host clade, with 58 of 78 birds (74%) infected and a total of 97 infections detected.…”
Section: Discussionmentioning
confidence: 92%
“…Both variables were obtained at 10 × 10 km resolution using the MODISTools R package (Tuck et al., 2014) and included as mean values, averaged across months when peak haemosporidian transmission is likely to occur in our study region: May–August. Finally, we included elevation (meters above sea level) as a predictor based on previous evidence that high‐elevation environments show increased prevalence of Leucocytozoon parasites (Barrow et al., 2019; Galen & Witt, 2014). Elevation for each site was extracted from Amazon Web Services (https://registry.opendata.aws/terrain-tiles/) using functions in the elevatr r package (Hollister & Shah, 2017).…”
Section: Methodsmentioning
confidence: 99%